Potential Development Analysis of Mangrove Ecosystem in Larompong Selatan, Luwu Regency - Kasim, Ompu Chandra; Tamsil, Andi; Hamsiah, Hamsiah (AgriSains, 2019)
The aims of this study were to examine the potential of mangroves and the factors causing mangrove damage, analyze the economic valuation of mangroves and formulate a mangrove ecosystem management strategy in South Larompong Subdistrict. Data collection was carried out by using purposive sampling with a number of respondents of 65 people. Data was then processed and analyzed descriptively, spatially, and Analytic Hierarchy Process (AHP). The results showed that there was a reduction in the mangrove area about 69.89 Ha from 2014-2018 due to the conversion of mangroves into ponds and settlements. The total economic value of mangroves in 2018 was Rp. 86.603.426.151, consisting of direct use value of Rp. 61.428.000.000, indirect use value (Indirect use value) of Rp. 7.638.926.151, option value of Rp. 15.114.000.000, and the existence value of Rp. 2.422.500.000. The instructions of mangrove management in South Larompong Subdistrict are planning the use of mangrove ecosystems, conservation and rehabilitation, providing extension on preservation of mangroves, optimizing the utilization of mangrove resources, strengthening community institutions, and law enforcement.Keywords: Mangrove Ecosystem, Level of Damage, Economic Valuation.